Long-Term Efficacy and Safety of Biodegradable-Polymer Biolimus-Eluting Stents: Main Results of the Basel Stent Kosten-Effektivitäts Trial–PROspective Validation Examination II (BASKET-PROVE II), A Randomized, Controlled Noninferiority 2-Year Outcome Trial. Issue 1 (6th January 2015) - Kaiser, Christoph; Galatius, Soeren; Jeger, Raban; Gilgen, Nicole; Jensen, Jan Skov; Naber, Christoph; Alber, Hannes; Wanitschek, Maria; Eberli, Franz; Kurz, David J.; Pedrazzini, Giovanni; Moccetti, Tiziano; et al.
Abstract : Background—: Biodegradable-polymer drug-eluting stents (BP-DES) were developed to be as effective as second-generation durable-polymer drug-eluting stents (DP-DES) and as safe >1 year as bare-metal stents (BMS). Thus, very late stent thrombosis (VLST) attributable to durable polymers should no longer appear. Methods and Results—: To address these early and late aspects, 2291 patients presenting with acute or stable coronary disease needing stents ≥3.0 mm in diameter between April 2010 and May 2012 were randomly assigned to biolimus-A9–eluting BP-DES, second-generation everolimus-eluting DP-DES, or thin-strut silicon-carbide–coated BMS in 8 European centers. All patients were treated with aspirin and risk-adjusted doses of prasugrel. The primary end point was combined cardiac death, myocardial infarction, and clinically indicated target-vessel revascularization within 2 years. The combined secondary safety end point was a composite of VLST, myocardial infarction, and cardiac death. The cumulative incidence of the primary end point was 7.6% with BP-DES, 6.8% with DP-DES, and 12.7% with BMS. By intention-to-treat BP-DES were noninferior (predefined margin, 3.80%) compared with DP-DES (absolute risk difference, 0.78%; −1.93% to 3.50%; P for noninferiority 0.042; per protocol P =0.09) and superior to BMS (absolute risk difference, −5.16; −8.32 to −2.01; P =0.0011). The 3 stent groups did not differ in the combined safety end point, with no decrease in events >1 year, particularly VLST with BP-DES. Conclusions—: In large vessel stenting, BP-DES appeared barely noninferior compared with DP-DES and more effective than thin-strut BMS, but without evidence for better safety nor lower VLST rates >1 year. Findings challenge the concept that durable polymers are key in VLST formation. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01166685. Abstract : Supplemental Digital Content is available in the text.